Geographies of poetry/poetries of geography. (January 2014) - Cresswell, Tim
This contribution is a reflection on the process of becoming a poet as a geographer. It charts my journey into the world of poetry and reflects on the cross-overs between academic geography and poetic practice in the past. It considers the way in which geography and poetry can inform each other in the practice of writing creatively, and tentatively suggests how this engagement might influence my on-going writing practice now and in the future.